Para-Phenylenediamine (PPD) in commercially available Henna preparations in Bangladesh - Saleh Mahmud, Sultan Abu; Ferdous, Tasnuva; Alam, Md Morshedul; Hossain, Md Shohag; Shozib, Habibul Bari; Khalil, Farzana; Akter, Faija; Hossain, Mohammad Nazir (Bioresearch Communications, 2021)
In Bangladesh Henna is one of the most popular cosmetic products. The leaves of Henna are dried to make powder on which oil or water is mixed to get a paste to stain the body or hair. Although the occurance of contact allergic dermatitis in natural Henna is not so common, but this risk is increased by adding para-Phenylenediamine (PPD), which is used to make the Henna color dark to deep black. According to Scientific Committee on Consumer Products (SCCP), para-Phenylenediamine (PPD) is treated as an allergen and is considered as a very strong potential skin sensitizer. The presence of PPD in the commercially used tube Henna increases the risk of allergic contact dermatitis and several cases have already been reported worldwide. For this study, about 10 Henna samples were randomly collected from 10 selected areas of Dhaka city. The presence of PPD in Henna samples was determined by using High Performance Liquid Chromatography (HPLC). The result showed the presence of PPD in all of the Henna samples at substantial concentrations, ranging between 79.12-204.77 mg/kg where the average range is 142.36 mg/kg, which is much higher than the permissible levels (<2% or 0.1 mg/m3). The finding suggests that there should be a regulation and monitoring condition for the production and distribution of these adulterated Henna products in Bangladesh. Bioresearch Commu. 8(1): 1088-1092, 2022 (January)